filmov
tv
Prove That 1/x + 1/y + 1/z = 0 Given 2^x = 3^y = 6^-z | Step-by-Step Solution'
Показать описание
Prove That 1/x + 1/y + 1/z = 0 Given 2^x = 3^y = 6^-z | Step-by-Step Solution"
Maths with Vinita Ma'am
SHOW THAT 1/x 1/y 1/z=0
Рекомендации по теме
0:15:10
Prove that (1/x + 1/y + 1/z) is greater than 3
0:04:40
In fig., AB || PQ || CD, AB = x units, CD = y units and PQ = z units, prove that 1/x+1/y=1/z.
0:05:57
Olympiad Question! Can you Prove: (1/x + 1/y = 1/z) IF (11^x = 17^y = 187^z)? | Simple Explanation
0:09:32
If y = √(1 - x/1 + x) , prove that (1 - x²) dy/dx + y = 0
0:09:41
If xyz=1, then prove that (1+x+y^-1)^-1 + (1+y+z^-1)^-1 + (1+z+y^-1)^-1 = 1.
0:07:25
If Y=√(1-x/1+x) , Prove that (1-x^2) dy/dx+Y =0 #class12maths #differentiation @mission_maths7451
0:05:06
If 2^x=3^y=6^-z then prove that 1/x+1/y+1/z=0
0:06:29
P𝐴, 𝑄𝐵 and 𝑅𝐶 are each perpendicular to 𝐴𝐶. prove that 1/x+1/y=1/z
0:22:18
Class 9 Math Exercise 4.2 Complete || 9 Class Mathematics Exercise 4.2 Question No.1 To 15
0:04:08
If PA, QB, and RC are each perpendicular to AC. Prove that 1/x + 1/z = 1 /y.
0:03:19
Prove that((x^(-1)+y^(-1))/x^(-1))^(-1)+((x^(-1)-y^(-1))/x^(-1))^(-1)=(2y^(2))/(y^(2)-x^(2)) | 8...
0:11:57
If 1/x-1/y∝1/(x-y) then prove that x∝y
0:02:33
If x root (1+y) + y root (1+x) = 0 Prove that dy/dx = -1/(1+x)2
0:05:00
Prove That 1/x + 1/y + 1/z = 0 Given 2^x = 3^y = 6^-z | Step-by-Step Solution'
0:08:26
In the given figure, PA, QB and RC are each perpendicular to AC. Prove that 1/x + 1/z =1/y
0:08:46
If y=e^tan^-1(x),prove that (1+x^2)Yn+2+(2(n+1)x-1)Yn+1 + n(n+1)Yn=0{based on Leibnitz Theorem}
0:04:34
Class 12- Differentiation-If x(1+y)^1/2 + y(1+x)^1/2=0 prove (1+x)^2dy\dx +1 =0
0:08:58
Proving a Quick and Easy Inequality (1+1/x)(1+1/y)≥9
0:01:04
1/x +1/y variation 1/x+y then prove that x+y variation x-y
0:08:25
1 + 1 = 3 Proof | Breaking the rules of mathematics
0:11:39
If 1/x-1/y∝1/(x-y) then prove that x+y∝x-y
0:09:17
If y = tan⁻¹(x), Prove that (1 + x²) d²y/dx² + (2x - 1) dy/dx = 0
0:24:39
If y= e^asin^-1x , prove that (1-x²)yn+2-(2n+1)xyn+1-(n²+a²)yn= 0. Hence find yn at x= 0
0:05:41
If y= x siny prove that dy/dx = y/[x(1- x cosy)]